2014
DOI: 10.3346/jkms.2014.29.11.1523
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphism in MicroRNA 604 with Susceptibility to Persistent Hepatitis B Virus Infection and Development of Hepatocellular Carcinoma

Abstract: MicroRNA polymorphisms may be associated with carcinogenesis or immunopathogenesis of infection. We evaluated whether the mircoRNA-604 (miR-604) polymorphism can affect the persistence of hepatitis B virus (HBV) infection, and the development to hepatocellular carcinoma (HCC) in patients with chronic HBV infection. A total of 1,439 subjects, who have either past or present HBV infection, were enrolled and divided into four groups (spontaneous recovery, chronic HBV carrier without cirrhosis, liver cirrhosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…These data suggest that the miR-1268a rs28599926 polymorphism should be an important genetic susceptible factor of cancer risk. Noticeably, previous studies have shown that rs11614913 (located in miR-196a-2), and rs2620381 (located in miR-627) modify the risk of some tumors such as colorectal cancer, lung cancer, and liver cancer [18,35,36]. Supporting aforementioned risk role, our report also exhibited that these two polymorphisms affected HCC risk, although there was no statistical significance observed according to the threshold of test power.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…These data suggest that the miR-1268a rs28599926 polymorphism should be an important genetic susceptible factor of cancer risk. Noticeably, previous studies have shown that rs11614913 (located in miR-196a-2), and rs2620381 (located in miR-627) modify the risk of some tumors such as colorectal cancer, lung cancer, and liver cancer [18,35,36]. Supporting aforementioned risk role, our report also exhibited that these two polymorphisms affected HCC risk, although there was no statistical significance observed according to the threshold of test power.…”
Section: Discussionsupporting
confidence: 49%
“…For example, in 2011, Zhang et al reported that rs11614913 and rs2910164 (located in miR-146a) did not affect HBV-related HCC risk [17]. Another recent report by Cheong et al [18] has shown that rs2368392 (located in miR-604, SNP19) increases susceptibility to persistent HBV and ultimately may increase HBV-related HCC. Our present study exhibited this polymorphism was not correlated with AFB1-HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…These results encourage future studies on the potential role of MALAT1 in CCA. In addition, increased levels of miR-604 and miR-551B in serum EVs from patients with CCA also provided excellent diagnostic capacities (up to 0.944) for CCA and some studies already started to evaluate their involvement in carcinogenesis and as diagnostic biomarkers [87][88][89][90]. Considering the high resistance of small ncRNAs to RNase degradation, additional efforts should be employed in order to validate their diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…As for the results in the METABRIC dataset, upstream modules of six latent pathways were almost identical and hence merged into one union (pathway 0, 1, 2, 7, 9, 14 in supplement (28) and the metastasis of colorectal cancer (29). MIR604 was differentially expressed in breast cancer (30).…”
Section: Orn Characterized Common Mechanisms In Cancermentioning
confidence: 85%